Enhancer of Zeste Homolog 2 (EZH2): From Glioblastoma Biology to Potential Epigenetic Therapy - Jan Grzegorzewski; Maria Lindner; Dagmara Lisińska; Aleksandra Majchrzak-Celińska (International Journal of Molecular Sciences, 2026)
Epigenetic dysregulation is a hallmark of glioblastoma (GBM) pathogenesis, with histone methylation playing a central role in chromatin remodeling and gene expression regulation. Enhancer of zeste homolog 2 (EZH2) is a key epigenetic regulator responsible for histone methylation. It primarily functions as a transcriptional repressor and regulates signaling pathways associated with tumor progression. Importantly, EZH2 is frequently recruited to long non-coding RNA (lncRNA) scaffolds, including HOTAIR and AGAP2-AS1, thereby enabling coordinated gene silencing by establishing repressive chromatin states. Although EZH2 expression is not consistently associated with overall survival in GBM, EZH2 remains a promising therapeutic target due to its roles in stemness and treatment resistance. This review summarizes current knowledge of EZH2 functions in normal and GBM cells, highlighting its complex functions and therapeutic potential. We also discuss the current status and limitations of EZH2-targeting therapies, including challenges related to blood–brain barrier penetration and clinical translation. Although a combination of EZH2 inhibitors and other epigenetic inhibitors may be beneficial in selected molecular contexts, its rationale depends on the underlying regulatory network. Future therapeutic development will require biomarker-driven patient stratification and precision medicine approaches to maximize clinical benefit in GBM.